ANALISIS BEBAN GEMPA TERHADAP KEKUATAN STRUKTUR BANGUNAN MULTI DEGRRE OF FREEDOME - Almufid Almufid (Jurnal Teknik, 2014)
S t r u c t u r al a n aly sis is pla n n e d p h a s e s o f a b uildin g , e s p e cially t h e hig h b uildin g s . I n t h e a n aly sis o f t h e s t r u c t u r e r e q uir e d t o f a cilit a t e t h e m o d elin g c alc ula tio n s r e fle c t a c t u al c o n ditio n s in t h e field , b o t h in s t r u c t u r e a n d in t h e lo a d e d . B e c a u s e alm o s t all p a r t s o f I n d o n e sia , in clu din g t h e e a r t h q u a k e - pro ne areas is a challenge for civil engineering planning in order to design earthquake resistant buildings. Indonesia has many experienced tremendous earthquake W ritin g t his p r o p o s al is in t e n d e d t o b e a ble t o k n o w t h e s t r e n g t h a n d structure of the response S trength multi degree of freedome, on soft ground, located in Tangerang when worn earthquake lateral loads, analysis is done with the help of the SAP program in 2000 ver.15, to get the style - the style such as: the base shear force, lateral force level, ro lling moment and lateral deviation. D y n a mic a n aly sis w a s c o n d u c t e d u sin g t h e r e s p o n s e s p e c t r u m a n aly sis , mass modeling performed with a lump mass models, the sum of the response variance is reviewed with some combinations, such as: CQC, SRSs and  ABSSUM.